(untitled) (Journal of the College of Basic Education, 2026)
Heritage tourism is one of the important social phenomena that contribute to encouraging travel, which helps the emergence of many social relations between different groups of society with the aim of entertainment and recreation, as well as that cultural tourism is an economic factor that contributes to maximizing the state’s imports by activating the service sector that achieves tourist satisfaction in order to ensure the continuity of tourism spending, hence the aim of the study to emphasize the importance of cultural tourist sites as educational, economic, cultural and study institutions. The relationship between cultural tourism sites and tourism development through the provision of the necessary services and facilities for them as well as encouraging governments to invest in the cultural tourism sector because of the ancient cultural sites in Baghdad, and from the research it was found that there are many cultural tourism sites in the province of Baghdad, some of which are qualified as a cultural center and others need many efforts to rehabilitate and stimulate tourism in order to help diversify the sources of state income and thus provide the necessary support to achieve a large profit margin Cultural tourism is a strategic alternative sector for many other sectors.